Supply Risk Management in Automotive Industry Supply Chain: A Grounded Theory - masuod simkhah; kamran Feizi (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2014)
This paper provides a process model for supply risk management in the automotive supply chain. Process model describes why the automobile manufacturer's entry into the supply risk management process and how automobile manufacturer manages supply risk. Rely on grounded theory and based on 13 qualitative in-depth interviews with 10 managers and experts in Iran's automotive industry supply chain, a theoretical framework for this issue is developed. Based on this framework, the category of perceptional process explains why the automobile manufacturer's entry into the supply risk management process and four categories of bedder factors, contingency factors, goals and process of facing to the supply risk explains how automobile manufacturer manages supply risk.